Optimal Restoration of Distribution Networks through Reconfiguration and Microgrid Formation - Macedo, Leonardo H. [UNESP] (2020)
This paper presents a new mixed-integer second-order cone programming model for the problem of optimal restoration of distribution networks that, besides network reconfiguration, also considers microgrid formation. General radiality constraints are used to allow the resulting microgrids to operate with single or multiple distributed generators. Furthermore, the proposed radiality formulation allows parts of the network to be de-energized. Thus, the alternative of disconnecting the loads from their nodes, which is used in some works to ensure radiality, may not be practical in some systems and, therefore, it is not considered in this paper. Tests are carried out using a 53-node system, and the results show that the proposed model can solve the problem at low computational times. It can also be verified that by allowing microgrid formation, more load can be reconnected to the system in the service restoration process.